2022
DOI: 10.3390/molecules27020491
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Clinical Evaluation of Cannabigerol (CBG) Produced via Yeast Biosynthesis: A Cannabinoid with a Broad Range of Anti-Inflammatory and Skin Health-Boosting Properties

Abstract: Cannabigerol (CBG) is a minor non-psychoactive cannabinoid present in Cannabis sativa L. (C. sativa) at low levels (<1% per dry weight) that serves as the direct precursor to both cannabidiol (CBD) and tetrahydrocannabinol (THC). Consequently, efforts to extract and purify CBG from C. sativa is both challenging and expensive. However, utilizing a novel yeast fermentation technology platform, minor cannabinoids such as CBG can be produced in a more sustainable, cost-effective, and timely process as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…CBG has shown to be more effective than CBD in reducing ultraviolet-light-induced inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6 [ 25 ]. CBG is more effective in reducing the Cutibacterium acne- induced interleukin 1-beta production in primary normal human epidermal keratinocytes [ 33 ]. Immunofluorescent staining of BAX revealed heavy expression of the pro-apoptotic mitochondrial pore protein from CBD treatment but not CBG; again, the DAPI staining show similar nuclear condensation patterns to the Ki-67 staining performed.…”
Section: Discussionmentioning
confidence: 99%
“…CBG has shown to be more effective than CBD in reducing ultraviolet-light-induced inflammatory cytokines, such as tumor necrosis factor-α and interleukin-6 [ 25 ]. CBG is more effective in reducing the Cutibacterium acne- induced interleukin 1-beta production in primary normal human epidermal keratinocytes [ 33 ]. Immunofluorescent staining of BAX revealed heavy expression of the pro-apoptotic mitochondrial pore protein from CBD treatment but not CBG; again, the DAPI staining show similar nuclear condensation patterns to the Ki-67 staining performed.…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, it seems noteworthy that CBG markedly, yet not significantly, increased the DAGLα/β to MAGL activity ratio ( Table 4 ) and doubled CB 1/2 binding ( Table 3 ), thus suggesting the selective enhancement of 2-AG signaling in human keratinocytes by this pCB. Moreover, the increase in the anti-inflammatory PEA following CBG treatment seems to be of note because a recent study showed that CBG, when applied topically, promotes skin health by reducing the appearance of redness and improving barrier function via anti-inflammatory activity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the researchers performed a single-blind clinical study on 20 healthy volunteers with sodium lauryl sulfate (SLS)-induced contact dermatitis and found that topical application of 0.1% CBG serum showed significantly lower trans-epidermal water loss (TEWL) values compared to placebo and untreated sites. Moreover, the CBG serum reduced redness and inflammation following 48 h treatment, and after 2 weeks of application, the skin condition almost returned to baseline levels of visual grade ( Perez et al, 2022 ).…”
Section: Known Phytocannabinoid Activity Against Inflammationmentioning
confidence: 91%
“…In a study that characterized the anti-inflammatory properties of CBG on human skin cells in vitro , it was demonstrated that CBG treatment reduced ROS levels in human dermal fibroblasts, better than vitamin C. CBG also protected human epidermal keratinocytes by inhibiting pro-inflammatory cytokines that were released following induction using UVA, UVB or Cutibacterium acnes exposure, including TNF-α, IL-1β, IL-6 and IL-8 ( Figure 1 ; Perez et al, 2022 ). Furthermore, the researchers performed a single-blind clinical study on 20 healthy volunteers with sodium lauryl sulfate (SLS)-induced contact dermatitis and found that topical application of 0.1% CBG serum showed significantly lower trans-epidermal water loss (TEWL) values compared to placebo and untreated sites.…”
Section: Known Phytocannabinoid Activity Against Inflammationmentioning
confidence: 99%